Вовка - добрая душа: стихи / Агния Барто ; рис. Ф. Лемкуля - Барто Агния Львовна (Детская литература, 1989)
Экземпляры: ф.7 (2018) / Инвентарный номер: 55130 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: Б 26 / ББК: 84(2Рос=Рус)